Organic and inorganic sublattice coupling in two-dimensional lead halide perovskites - Jianhui Fu; Tieyuan Bian; Jun Yin; Minjun Feng; Qiang Xu; Yue Wang; Tze Chien Sum (Nature Communications, 2024)
Abstract Two-dimensional layered organic-inorganic halide perovskites have successfully spread to diverse optoelectronic applications. Nevertheless, there remain gaps in our understanding of the interactions between organic and inorganic sublattices that form the foundation of their remarkable properties. Here, we examine these interactions using pump-probe spectroscopy and ab initio molecular dynamics simulations. Unlike off-resonant pumping, resonant excitation of the organic sublattice alters both the electronic and lattice degrees of freedom within the inorganic sublattice, indicating the existence of electronic coupling. Theoretical simulations verify that the reduced bandgap is likely due to the enhanced distortion index of the inorganic octahedra. Further evidence of the mechanical coupling between these two sublattices is revealed through the slow heat transfer process, where the resultant lattice tensile strain launches coherent longitudinal acoustic phonons. Our findings explicate the intimate electronic and mechanical couplings between the organic and inorganic sublattices, crucial for tailoring the optoelectronic properties of two-dimensional halide perovskites.